Positioning buried utilities in difficult environments - Zhang, Penghe; Hancock, Craig; Lau, Lawrence; Roberts, Gethin Wyn; de Ligt, Huib; Quan, Yiming (2016)
Recently an increasing number of underground pipes have been established, particularly in city centres, for different applications such as sewage, electricity, gas, water and drainage. How to detect and make a precise 3-dimensional survey of buried pipelines has become a focused issue. This paper first of all reviews four trenchless technologies for locating buried utilities with an emphasis on describing their application and limitations. It is found that there is no single technology, which is able to locate all underground utility service infrastructures, particularly for deep buried plastic pipes. Meanwhile, these trenchless detection technologies need to be integrated with positioning technologies to create maps for buried utilities. One of the most attractive positioning technologies for providing absolute global position is Global Navigation Satellite Systems (GNSS). However a large percentage of buried utilities are in urban areas, where is not ideal for GNSS positioning technology. This paper evaluates the performance of single and multi GNSS constellations by carrying out a test in a controlled environment. The results show that using combined GNSS systems improve availability in urban canyons compared with using GPS alone. In addition, this paper describes an inertial based pipeline positioning technology called ‘Ductrunner’, which can locate and position the buried objects in spite of the material and depth without extra positioning systems. An approximately 30m long test pipeline has been established to evaluate the performance of Ductrunner. The maximum positioning errors are found to be 8cm in plan and 4cm in height. This shows that this technology is very promising for measuring deep pipes over relatively short distances.